'A NEW SEASON FOR PLANNING': URBAN GARDENING AS INFORMAL PLANNING IN ROME. Issue 2 (June 2016) - Certomà, Chiara
ABSTRACT: This article investigates the relationship between urban gardening and planning by building upon the results of field research on gardening initiatives in the city of Rome, Italy. The work is aimed at suggesting that, while often associated in geography and planning literature with urban informality practices (e.g. accidental city or self‐made urbanism), urban gardening actually presents the character of a distinctive form of people's interaction with urban space, here defined as "informal planning". This includes practices that are intentionally put forward by local dwellers with the intention of urban space planning and organizing public life in the absence of legal definition, guidance and funds provided by public authorities or the private sector. Urban gardening cases in Rome exemplify the emergence of informal planning and show how, by questioning the counterplanning tradition that understands urban gardening as an antagonist spatial practice opposing institutional planning, informal planning can open up collaborative possibilities. A new mode of interaction between citizens' agency and the formal planning initiatives of local administration can lead to creative solutions to address some of the problems associated with the neoliberal transformation of the city space, most notably the decrease in public space and its deterioration.